2004
DOI: 10.1111/j.1464-410x.2004.04829.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization analysis of matched primary tumour and lymph‐node metastasis of D1 (pT2–3pN1M0) prostate cancer

Abstract: nuclei obtained from matched primary tumours and their lymph node metastases. RESULTSOf the 28 suitable cases it was possible to complete the study in 18 pairs of matched tissues; the remainder were excluded because of insufficient tissue or poor preservation of at least one of the tissues. There was cytogenetic change (aneuploidy) in 16 of the 18 primary tumours, the most common being monosomy 8, detected in 14, followed by trisomy 7, in 13 aneuploid tumours. All lymph node metastases were aneuploid by FISH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, some studies showed that metastases were high similar to their matched primary cancers at the levels of cytologic features [25,26], cytogenetic alterations [27][28][29][30][31][32][33][34][35], DNA changes including aneuploidy, and index [36][37][38][39][40][41][42], gene analyses including mutations [43][44][45][46][47][48][49][50][51][52][53], profiles [18,[54][55][56][57], and epigenetic and transcriptive changes [58][59][60][61][62], proteomic profiling [61,63] and expression [64][65][66][67][68][69][70][71]…”
Section: Similarities Between Primary Tumors and Matched Metastases Amentioning
confidence: 99%
“…On the one hand, some studies showed that metastases were high similar to their matched primary cancers at the levels of cytologic features [25,26], cytogenetic alterations [27][28][29][30][31][32][33][34][35], DNA changes including aneuploidy, and index [36][37][38][39][40][41][42], gene analyses including mutations [43][44][45][46][47][48][49][50][51][52][53], profiles [18,[54][55][56][57], and epigenetic and transcriptive changes [58][59][60][61][62], proteomic profiling [61,63] and expression [64][65][66][67][68][69][70][71]…”
Section: Similarities Between Primary Tumors and Matched Metastases Amentioning
confidence: 99%